Policy note on Kenya’s draft agriculture sector Gender Policy - Waithanji, Elizabeth M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2021)
The Agriculture Sector Gender Policy has been reviewed and revised through six key thematic areas – Gender and Social Inclusion (GeSI) and the five thematic areas in Agriculture that intersect with gender, namely, Agriculture Value Chain Development (AVCD); Food and Nutrition Security (FNS); Climate Change (CC); National and Devolved Governance; and the Strategic Analysis Knowledge Support System (SAKSS), in eight Regional Economic Blocs (REB). Evidence of gender gaps and their determinants in agricultural productivity in Africa exists. Data has demonstrated that even the slightest reduction in the gender gap in agriculture results in huge economic benefits that elevate millions of people out of poverty. Women and men converged in their observation that the ministry of Agriculture, Livestock, Fisheries and Cooperatives, the ministry of Public Service Youth and Gender, and their corresponding county level departments were the stakeholders for who the Agriculture Sector Gender policy is most relevant. They diverged in their recognition of private sector stakeholders with men recognizing NGOs, CBOs and FBOs more than women and women recognizing financial institutions more than men. GeSI, devolved function and AVCD were ranked highest by both women and men, but women ranked climate change higher than men, whereas men ranked SAKKS higher than women. FNS was ranked low by women and men stakeholders, probably because it is a relatively new theme and poorly understood. The policy has identified the following: Capacity, and capacity gaps, of actors of policy implementation and ways of addressing the gaps; Opportunities for private and public partnerships in the implementation of the policy; and Policy document custodians prior to and during implementation.